2013
DOI: 10.2152/jmi.60.197
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine string protein 1 (CSP1) modulates insulin sensitivity by attenuating glucose transporter 4 (GLUT4) vesicle docking with the plasma membrane

Abstract: : Insulin stimulates glucose transporter 4 (GLUT4) vesicle recruitment from its intracellular storage site to the plasma membrane. Cysteine string protein 1 (CSP1) is a SNARE-binding protein involved in the vesicular trafficking of neurotransmitters and other exocytic processes. In this study, we investigated the involvement of CSP1 in insulin-dependent GLUT4 recruitment in 3T3-L1 adipocytes. Over-expression of wild-type CSP1 led to attenuated insulin-stimulated glucose uptake without any change in GLUT4 conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Elevated circulating estrogen levels have been related to insulin resistance in pregnancy ( 39 ). After binding to the estrogen receptor, estradiol may decrease insulin sensitivity through reducing the expression of the insulin sensitive membrane transporter - glucose transporter 4 in adipose tissue and muscle ( 40 , 41 ). Two studies on cord blood estradiol levels in GDM showed inconsistent findings ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated circulating estrogen levels have been related to insulin resistance in pregnancy ( 39 ). After binding to the estrogen receptor, estradiol may decrease insulin sensitivity through reducing the expression of the insulin sensitive membrane transporter - glucose transporter 4 in adipose tissue and muscle ( 40 , 41 ). Two studies on cord blood estradiol levels in GDM showed inconsistent findings ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%